Genetic Regulatory Networks of Apolipoproteins and Associated Medical Risks - Basavaraju, Preethi; Balasubramani, Rubadevi; Kathiresan, Divya Sri; Devaraj, Ilakkiyapavai; Babu, Kavipriya; Alagarsamy, Vasanthakumar; Puthamohan, Vinayaga Moorthi (Frontiers in Cardiovascular Medicine, 2022)
Apolipoproteins are the lipoprotein family proteins that play key roles in transporting lipoproteins all over the body. There are nearly more than twenty members reported in the apolipoprotein family, among which the A, B, C, E and L play major roles in contributing genetic risks to several disorders. Amongst these genetic risks the Single nucleotide polymorphisms (SNPs), involving the variation of single nucleotide base pairs, and their contributing polymorphisms play crucial roles in the apolipoprotein family and its concordant disease heterogeneity that have predominantly recurred through the years. In this review we have contributed a handful of information on such genetic polymorphisms that include APOE, ApoA1/B ratio and A1/C3/A4/A5 gene cluster based population genetic studies carried throughout the world, to elaborately discuss the effects of various genetic polymorphisms in imparting various medical conditions including cardiovascular, stroke, Alzheimer’s disease, Diabetes, Vascular complications and other associated risks.